STRATEGI KOMUNIKASI PT.CHEVRON PACIFIC INDONESIA DALAM IMPLEMENTASI PERATURAN LALU LINTAS INTERNAL DI CAMP CHEVRON RUMBAI - Senna Aristanto; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
PT. Chevron Pacific Indonesia is one of the largest energy companies in the world. This company has a very unique traffic code that applies at Chevron Camp as it stands in stark contrast to the hustle and bustle of traffic outside Chevron Camp and lacks discipline. Chevron Camp's internal traffic regulations can be implemented with discipline by every family of Chevron Camp residents who are said to be effective because of the proper socialization steps from PT Chevron Pacific Indonesia. The aims of this study are to know the communicator strategy, the audience target, communication message and communication media in the implementation of traffict internal regulation in Camp Chevron Rumbai.This study uses qualitative research methods by means of descriptions in the form of words and language. The subject of this research is the employees of PT. Chevron Pacific Indonesia which enforces internal traffic regulations at Camp Chevron Rumbai. Researchers used research informants through key persons, which were 8 formal and informal figures. Data collection techniques by interview, observation and documentation. The data analysis technique in this study refers to the interactive model of Huberman and Miles. The results of this study state that the communicator strategy in conveying the socialization is the Head and Security members of PT CPI. In addition, it also collaborates with the Police and local governments such as Districts and Villages in delivering messages. Audience communication strategy, PT. Chevron Pacific Indonesia divides the target audience into two, namely residents of housing in Camp Rumbai and the general public. Communication message strategy, PT. Chevron Pacific Indonesia in assessing the objectives of the socialization expects a response from the target audience. To achieve this goal, using media that emphasizes the content of the message conveyed in the form of socialization of the traffic regulations that are applied, calls for obeying the traffic rules in Camp Rumbai and the sanctions that will be given if these regulations are violated. The communication media strategy used in spreading messages uses media in the form of: print media such as the Chevron Bulletin, traffic signs and banners and face-to-face such as socialization to schools both inside Camp Rumbai and outside Camp Rumbai. Keyword: Strategy Communication, internal traffic , PT.Chevron Pacific Indonesia